2010
DOI: 10.1175/2010jpo4340.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Roughness Length Model and Sea Surface Properties with Data from the Baltic Sea

Abstract: The exchange of momentum between the oceans and atmosphere is important for many atmospheric and oceanic processes and is mainly governed by the roughness of sea surface. The roughness can be expressed by a roughness length z 0 . A roughness length model, based on the concept that z 0 is determined by stochastic wave breaking, is presented. The model performance is evaluated using measurements from the Ö stergarnsholm site, in the Baltic Sea, and pertinent information from other recent investigations. The wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Moreover, estimating the directional difference requires extra information (the wind direction) to be obtained from the wind field or from a spectral partitioning of the spectrum. Such partitioning would also be required for other wave parameters, such as the energy ratio of swell and local wind sea [ Carlsson et al , 2010]. Both partitioning and wind information can be avoided by using the wave directional spreading.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, estimating the directional difference requires extra information (the wind direction) to be obtained from the wind field or from a spectral partitioning of the spectrum. Such partitioning would also be required for other wave parameters, such as the energy ratio of swell and local wind sea [ Carlsson et al , 2010]. Both partitioning and wind information can be avoided by using the wave directional spreading.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the model seems particularly sensitive to changes in the parameter c_sea, describing the surface area density of the waves over sea, used for the calculation of roughness length. The roughness of the sea surface steers the exchange of momentum, moisture and heat between ocean and atmosphere (Carlsson et al, 2010;Vickers and Mahrt, 2010). Thévenot et al (2016) demonstrated that an increase in sea surface roughness may generate higher momentum fluxes, impacting low-level atmospheric dynamics, particularly affecting wind speeds, and that a proper representation of the sea surface roughness may lead to a better localization of heavy precipitation.…”
Section: Model Behaviour For Different Subregionsmentioning
confidence: 99%
“…These regions are characterized by particularly stable stratified atmospheric conditions. For these, the model has already proved to be highly sensitive to tkhmin (Cerenzia et al, 2014;Buzzi et al, 2011), producing excessive mixing during periods with highly stable stratification and a consequent overestimation of temperatures. Basically, higher values of tkhmin produce exaggerated mixing, leading to more cloud formation, more similarly to observations, that otherwise the model is not able to reproduce.…”
Section: Model Behaviour For Different Subregionsmentioning
confidence: 99%
“…Roughness length is determined from c_sea and the roughness of the sea surface guides the exchange of momentum, moisture, and heat between ocean and atmosphere. Therefore, an increase in c_sea may induce higher magnitude momentum fluxes, modifying low-level atmospheric dynamics, specifically affecting wind speed and heavy precipitation [77,78] . Differential heating of the land surface causes regional uncertainties which stimulate moist convection by liberating latent heat.…”
Section: Physical Interpretation Of Parameter Sensitivitymentioning
confidence: 99%